A transformada de laplace em sistemas de equações diferenciais lineares - Santos, Erika Oliveira dos (Universidade Federal Rural do Semi-Árido, 2019)
The present work aims to solve systems of linear differential equations using the Laplace transform as a resolution method. The sequence work is bibliographic. Prior to addressing the main theme, a review of introductory concepts was performed as a prerequisite to the subject of the study. In addition, the definitions, examples, applications pertinent to ordinary differential equations, and theorems in which they have been proved, were presented in order to serve as support for theoretical foundation and motivation for readers in this area.
Monografia
Keywords: Transformada de laplace; Sistemas de equações diferenciais lineares; Aplicações; Laplace transform; Systems of Linear differential equations; Applications; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA